Credit Risk, Financial Inclusion and Microfinance Performance in Pakistan: An Empirical Analysis - Khalid, Hafeez; Salawati, Sahari (Human Resource Management Academic Research Society, 2025)
This study examines the impact of credit risk and financial inclusion on the performance of microfinance institutions (MFIs) in Pakistan, using a pooled OLS regression approach. The analysis is based on balanced panel data (2012–2021) for 19 MFIs obtained from the Pakistan Microfinance Network (PMN). The study employs portfolio at risk (PAR) and non-performing loans (NPL) as proxies for credit risk, while operational efficiency (OPREFF) and annual percentage rate (APR) represent financial inclusion. The dependent variable, MFI performance, is measured using return on assets (ROA), return on equity (ROE), and operational self-sufficiency (OSS). Additionally, firm size (FSIZE), firm age (FAGE), capital intensity (CAPINT), and leverage (LEV) are incorporated as control variables. The findings indicate that PAR has a significant negative effect on ROA, ROE, and OSS, highlighting the detrimental impact of rising credit risk on MFI performance. However, NPL does not exhibit a significant impact, suggesting that non-performing loans alone may not immediately affect financial stability. In contrast, OPREFF positively influences all three performance indicators, confirming that operational efficiency plays a critical role in enhancing MFI profitability and sustainability. APR negatively affects performance, suggesting that higher interest rates may reduce borrower repayment capacity and increase financial distress. Among the control variables, FSIZE and FAGE positively contribute to MFI performance, while CAPINT and LEV remain statistically insignificant. These results underscore the importance of effective credit risk management, cost efficiency, and balanced interest rate policies in ensuring the sustainability of MFIs. The study provides valuable insights for policymakers, MFI managers, and stakeholders in designing strategies that promote financial inclusion while maintaining institutional stability. Future research may explore the role of macroeconomic factors and regulatory policies in shaping MFI performance.